2021
DOI: 10.3389/fmed.2021.684058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Qigong Exercise for Treatment of Fatigue: A Systematic Review and Meta-Analysis

Abstract: Objective: Several studies suggested that Qigong exercise (QE) can relieve fatigue in patients diagnosed with various diseases. Our review aimed to evaluate the efficacy of QE for alleviating fatigue.Methods: A related literature search was performed in the PubMed, Web of Science, Embase, Cochrane Library, China Biology Medicine disc (CBM), China National Knowledge Infrastructure (CNKI), Wanfang, and VIP data bases from inception to November 2020. Information on fatigue, malaise, tiredness, and Qigong research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Wang, et al [27] examined the results of 16 randomized control trials involving patients with cancer chronic fatigue syndrome and other diseases to determine whether qigong exercises had any effect on total fatigue intensity. They found that the qigong exercise group had significant improvement (p < 0.00001).…”
Section: Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Wang, et al [27] examined the results of 16 randomized control trials involving patients with cancer chronic fatigue syndrome and other diseases to determine whether qigong exercises had any effect on total fatigue intensity. They found that the qigong exercise group had significant improvement (p < 0.00001).…”
Section: Fatiguementioning
confidence: 99%
“…In the West, it is sometimes used in conjunction with mainstream medicine as a supplementary tool to treat symptoms of various diseases and ailments [1][2][3][4][5][6][7][8][9][10]. Numerous studies have found that qigong can aid in the treatment of arthritis [11], back pain [12], cancer [13][14][15][16][17], cognitive impairment [18,19], Covid-19 [20,21], COPD [22], depression and anxiety [23][24][25][26], fatigue [27], hypertension [28,29], muscle strength and posture [30], Parkinson's disease [31,32], stroke [33], and tertiary-care pain management [34].…”
Section: Introductionmentioning
confidence: 99%
“…CAM encompasses a variety of traditional Chinese medicine (TCM) therapies such as herbal remedies, acupuncture, and homeopathy [16]. Literature reviews provide evidence for the effectiveness of CAM therapy in relieving symptoms of CFS [17][18][19] and Qigong as a CAM modality that is commonly used in CFS treatment [20,21]. Qigong (pronounced: chee-gong) is a systematic mind/ body exercise with restorative benefits and potentiates the whole person.…”
Section: Introductionmentioning
confidence: 99%
“…Qigong is a mind-body exercise originating in China which incorporates slow, coordinated movements, breath training, heightened somatic awareness, and mental focus and imagery ( Klein, 2017 ). Recent systematic reviews have suggested that Qigong may be beneficial for improving overall quality of life, mood, sleep, and symptoms such as fatigue in cancer patients ( Klein et al, 2016 ; Wayne et al, 2018 ; Kuo et al, 2021 ; Wang R. et al, 2021 ). In a pilot study conducted by our group—the parent study for the data presented here—we evaluated the impact of a 12-week Qigong intervention in BCS with PPSP.…”
Section: Introductionmentioning
confidence: 99%